The Practice of Islamic Philanthropy in Indonesian History a Book Review of (Filantropi Islam: Sejarah dan Kontestasi Masyarakat Sipil dan Negara di Indonesia) - Abdillah, Faisal Nuja (Al-Mazaahib: Jurnal Perbandingan Hukum, 2024)
Philanthropic activities have a major contribution to the development of social welfare in Indonesia. The practice of philanthropy has a positive impact on people's lives both in the social and economic spheres. As the majority religious group in Indonesia, Muslims have contributed significantly to improving the welfare of society through Islamic philanthropy movements such as waqf, sadaqah, zakat and infaq. The Islamic philanthropy movement in Indonesia has been massively practiced since the Dutch colonial period until today. The movement has gone through various changes and dynamics in its implementation. The development and dynamics of the practice of Islamic philanthropy in Indonesia could be seen from generation to generation, starting from the Dutch colonial period to the post-reform period. This is a book review of the book Islamic Philanthropy: History and Contestation of Civil Society and the State in Indonesia by Amelia Fauzia. This book review recommends that this book should be widely read by those who seek to deepen knowledge about the practice of Islamic philanthropy in Indonesia from the Dutch colonial period to the reformation era. Kegiatan filantropi memiliki andil besar dalam pengembangan kesejahteraan masyarakat di Indonesia. Praktik filantropi memberikan dampak positif bagi kehidupan masyarakat baik pada bidang sosial maupun ekonomi. Sebagai kelompok agama mayoritas di Indonesia, umat Islam telah memberikan kontribusi besar dalam upaya meningkatkan kesejahteraan masyarakat melalui gerakan filantropi Islam seperti wakaf, sedekah, zakat, dan infaq. Gerakan filantropi Islam di Indonesia secara masif dilakukan sejak masa penjajahan Belanda hingga sampai saat ini. Gerakan tersebut telah melewati berbagai dinamika dalam pelaksanaannya. Perkembangan dan dinamika praktik filantropi Islam di Indonesia dapat di lihat dari masa ke masa, mulai pada saat masa penjajahan belanda hingga masa pasca reformasi. Artikel ini merupakan book review atas buku Filantropi Islam: Sejarah dan Kontestasi Masyarakat Sipil dan Negara di Indonesia karya Amelia Fauzia. Book review ini merekomendasikan buku ini untuk dibaca oleh kalangan yang ingin memperdalam pengetahuan mengenai praktik filantropi Islam di Indonesia dari masa pemerintahan Belanda, hingga masa era reformasi.